Comment: "An Investment Paradox" - Ghidini, Giulio (Journal of Financial and Quantitative Analysis, 1977)
Prof. A. Carol examined a replacement problem in a paper published in the January 1972 issue of this journal.The aim of the author seems to be to obtain a precise insight in the pattern of quantities to be considered to take a rational decision.